Cycloisomerization of Carbamoyl Chlorides in Hexafluoroisopropanol: Stereoselective Synthesis of Chlorinated Methylene Oxindoles and Quinolinones. (16th July 2021) - Rodríguez, José F.; Zhang, Anji; Bajohr, Jonathan; Whyte, Andrew; Mirabi, Bijan; Lautens, Mark
Abstract: Hexafluoroisopropanol (HFIP) was employed as an additive for the generation of 3‐(chloromethylene)oxindoles via the chloroacylation of alkyne‐tethered carbamoyl chlorides. This reaction avoids the use of a metal catalyst and accesses products in high yields and stereoselectivities. Additionally, this reaction is scalable and proved amenable to a series of product derivatizations, including the synthesis of nintedanib. The reactivity of alkene‐tethered carbamoyl chlorides with hexafluoroisopropanol (HFIP) was harnessed towards the synthesis of 2‐quinolinones. Abstract : The application of hexafluoroisopropanol (HFIP) as a reagent in the cycloisomerization of alkyne‐tethered carbamoyl chlorides is demonstrated. The chlorinated methylene oxindole products are obtained in excellent E ‐selectivities. This reactivity was also extended towards the synthesis of chlorinated methylene pyrrolidones and 2‐quinolinones.